Pengaruh Project-Based Learning dan Jenis Kelamin terhadap Keaktifan Belajar Siswa Kelas XI di MA Nurul Ihsan Lombok Tengah - Hadi, Muhammad Fajrul; Mariono, Andi; Kristanto, Andi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to determine the influence of Project-Based Learning (PjBL) and gender on students' active learning. The type of research carried out was quantitative using a quasi experimental method. The research design used was a posttest only control group design. The research was conducted on the subjects of class XI students at MA Nurul Ihsan, Central Lombok, a total of 68 students. Researchers divided research subjects into two study groups. The first group is students who are taught using PjBL as an experimental group. The second group is students who carry out conventional learning activities. Each group consisted of 18 male students and 16 female students. Data collection was carried out using the observation method. Hypothesis testing was carried out using the ANOVA test. The findings from this research show that there is an influence of PjBL and gender on students' active learning. Overall, students who are taught using PjBL have better learning activity than students who are taught conventionally. Other findings in this research show that female students have better learning activity than male students.